STRATEGI KOMUNIKASI BAHASA JEPANG (STUDI KASUS MAHASISWA SEMESTER EMPAT DAN MAHASISWA SEMESTER ENAM PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU) - Amin, Saddam; Budiani, Dini; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: The purpose of this research is to discover communication strategy used by japanese learners. This research divided the learners onto two groups, Elementary level learners and intermediate level learners. On this research, student on 4th semesters are elementary level learners while 6th semesters students are intermediate level learners; each group will be taken 10 people as object which make 20 people in total. Data collected using roleplay as a form of conversation As results this research found that elementary level learners tend to use intralingual strategy asking for help and intralingual make new world strategy; intermediate level learners tend to use intralingual restructuritation strategy. Generally speaking, intralingual strategy often used by both groups followed by form reduction strategy. One of the reason why that happened is, even though student already understood the language most of them practice their japanse as a tool to communication. This makes the student to feel nervous or doubt what kind of words or grammar they should use next.keywords: communication, strategy, intermediat, elementary, learners, japanese